Homeowner's Guide to Fungicides for Lawn and Landscape Disease Management - Philip F. Harmon; Aaron J. Palmateer; Rachel Ribbeck (EDIS)
PP-233, a 5-page fact sheet by Philip Harmon, Aaron Palmateer, and Rachel Ribbeck, provides information homeowners should know before using fungicide products to manage diseases in the home lawn and landscape. It describes what a disease is, the "disease triangle" explaining how diseases occur, diagnosis and prevention, and fungicide facts. Includes two tables, one listing fungicide products marketed toward homeowners, and one listing fungicide products marketed toward professional pesticide applicators. Published by the UF Department of Plant Pathology, September 2006.